FGF10 and the Mystery of Duodenal Atresia in Humans - Teague, Warwick J.; Jones, Matthew L. M.; Hawkey, Leanne; Smyth, Ian M.; Catubig, Angelique; King, Sebastian K.; Sarila, Gulcan; Li, Ruili; Hutson, John M. (Frontiers in Genetics, 2018)
Background: Duodenal atresia (DA) is a congenital obstruction of the duodenum, which affects 1 in 7000 pregnancies and requires major surgery in the first days of life. Three morphological DA types are described. In humans, the association between DA and Down syndrome suggests an underlying, albeit elusive, genetic etiology. In mice, interruption of fibroblast growth factor 10 (Fgf10) gene signaling results in DA in 30-50% of embryos, supporting a genetic etiology. This study aims to validate the spectrum of DA in two novel strains of Fgf10 knock-out mice, in preparation for future and translational research. Method: Two novel CRISPR Fgf10 knock-out mouse strains were derived and embryos generated by heterozygous plug-mating. E15.5-19.5 embryos were genotyped with respect to Fgf10 and micro-dissected to determine the presence and type of DA. Results: 127 embryos (32 wild-type, 34 heterozygous, 61 null) were analyzed. No wild-type or heterozygous embryos had DA. However, 74% of Fgf10 null embyros had DA (49% type 1, 18% type 2 and 33% type 3). Conclusion: Our CRISPR-derived strains showed higher penetrance of DA due to single-gene deletion of Fgf10 in mice than previously reported. Further, the DA type distribution in these mice more closely reiterated that observed in humans. Future experiments will document RNA and protein expression of FGF10 and its key downstream signaling targets in normal and atretic duodenum. This includes exploitation of modern, high-fidelity developmental tools, e.g. Fgf10flox/+_tomatoflox/flox mice.